2013
DOI: 10.1186/2051-1426-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD-1 antibody significantly increases therapeutic efficacy of Listeria monocytogenes (Lm)-LLO immunotherapy

Abstract: BackgroundOne of the significant tumor immune escape mechanisms and substantial barrier for successful immunotherapy is tumor-mediated inhibition of immune response through cell-to-cell or receptor/ligand interactions. Programmed death receptor-1 (PD-1) interaction with its ligands, PD-L1 and PD-L2, is one of the important strategies that many tumors employ to escape immune surveillance. Upon PD-Ls binding to PD-1, T cell receptor (TCR) signaling is dampened, causing inhibition of proliferation, decreased cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 32 publications
4
56
0
Order By: Relevance
“…To achieve the goal of in vivo DC targeted antigen delivery, the HPV16 E7 long peptide (amino acid [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] containing the dominant T cell epitopes was fused to the single-chain fragment variable (scFv) specific for DEC-205 (aDEC205) using a protein assembly strategy based on the SpyCatcher-SpyTag system as described previously. 26 The SpyTag was genetically fused to the C-terminus of aDEC205 to obtain aDEC205-SpyTag and the E7 long peptide was added to the C-terminus of SpyCatcherDN to obtain Sc-E7, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve the goal of in vivo DC targeted antigen delivery, the HPV16 E7 long peptide (amino acid [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] containing the dominant T cell epitopes was fused to the single-chain fragment variable (scFv) specific for DEC-205 (aDEC205) using a protein assembly strategy based on the SpyCatcher-SpyTag system as described previously. 26 The SpyTag was genetically fused to the C-terminus of aDEC205 to obtain aDEC205-SpyTag and the E7 long peptide was added to the C-terminus of SpyCatcherDN to obtain Sc-E7, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…26 7 d later, the DLNs from the immunized mice were isolated and digested into single-cell suspensions, and then stimulated with 5 mg/mL E7 [49][50][51][52][53][54][55][56][57] peptide in a U-bottom 96-well plate for 6 h. The IFNg producing CD8 C T cells were then determined and analyzed by intracellular staining and flow cytometry. As shown in Fig.…”
Section: Targeting Tumor Vaccine Generates Significantly Enhanced mentioning
confidence: 99%
“…Furthermore, analysis of PBMCs following administration of a glypcian-3 (GPC3) peptide vaccine in advanced or metastatic HCC revealed a high expression of PD-1 on peptide-specific CD8 + T-cells [84]. Similarly, immunotherapy using Listeria monocytogenes (Lm)-LLO can be improved by reduction of the Tregs and MDSCs, but as it is also associated with the upregulation of PD-L1 on immune cells, in particular macrophages, the use of antibodies blocking the PD-1:PD-L1 axis is justified [85]. Indeed, administration of the PD-1 blocking antibody in combination with the cancer vaccine caused increased tumor regression.…”
Section: Concurrent Combination Of Immunomodulatory Antibodies With Vmentioning
confidence: 99%
“…We and others have previously demonstrated that successful cancer immunotherapy requires simultaneous targeting of both effector and suppressor arms of the immune system (41)(42)(43)(44)(45). Because OX40 leads to increased INFg expression in the periphery and within the tumor microenvironment (16,17) and INFg promotes the induction of IDO, we hypothesized that OX40-based antitumor immunotherapy could be improved by reducing immune suppression through inhibition of IDO.…”
Section: Introductionmentioning
confidence: 99%